2015
DOI: 10.3390/jmse4010001
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental and Numerical Study of Long Wave Run-Up on a Plane Beach

Abstract: This research is to facilitate the current understanding of long wave dynamics at coasts and during on-land propagation; experimental and numerical approaches are compared against existing analytical expressions for the long wave run-up. Leading depression sinusoidal waves are chosen to model these dynamics. The experimental study was conducted using a new pump-driven wave generator and the numerical experiments were carried out with a one-dimensional discontinuous Galerkin non-linear shallow water model. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…Others have achieved reasonable scaling using other generation methods, see e.g. the pump generated tsunami experiments by Rossetto et al (2011), Goseberg et al (2013), Goseberg (2013), Drähne et al (2016) and .…”
Section: Introductionmentioning
confidence: 99%
“…Others have achieved reasonable scaling using other generation methods, see e.g. the pump generated tsunami experiments by Rossetto et al (2011), Goseberg et al (2013), Goseberg (2013), Drähne et al (2016) and .…”
Section: Introductionmentioning
confidence: 99%
“…6 pointed out that solitary wave was barely justified for geophysical scale tsunami modelling just as meaningful evidence supporting the difference between N-wave and solitary wave has been reported 16 – 19 . Accordingly, we generate a single-period sinusoidal wave on the flat seabed, which can be found through recent tsunami-related works 20 22 . The incident wave is designed to be with .…”
Section: Methodsmentioning
confidence: 99%
“…By raising or lowering the water level in the chamber through the adjustment of its relative vacuum, a corresponding wave trough or wave crest is then created [32]. On the other hand, Goseberg and colleagues [33][34][35] were able to generate much longer waves with arbitrary waveforms by employing four high-capacity pipe pumps to control the acceleration and deceleration of water in a closed-circuit wave flume. Specifically, waves are actually induced by the produced bidirection current.…”
Section: Introductionmentioning
confidence: 99%
“…This makes them more suitable for laboratory tsunami research. For instance, some direct applications of these wave generators to the study of tsunami runup are reported in [32,35,38].…”
Section: Introductionmentioning
confidence: 99%